Antifouling Activity of Cymodecea rotundata and Halodule pinifolia at Pulau Morotai. Issue 1 (February 2021) - Nurafni; Nur, R M; Koroy, K; Alwi, D; Muhammad, S; Eso, N
Abstract: Biofouling is the attachment of the organism to the surface of the submerged in water. The presence of a fouling organism causes losses in the form of accelerating damage and adding to the burden of the ship/ boat. The activity of biofouling can be avoided by using environmentally friendly antifouling paint. Some marine organisms, such as mangroves and seagrass, are reported to have antifouling activity. The purpose of this study was to determine the antifouling activity of seagrass C. rotundata and H. pinifolia and to identify bioactive compounds contained in C. rotundata and H. pinifolia . Based on the result of the research, the yield of C. rotundata extract was 5.96% and H. Pinifolia 19.23%. The activity of antifouling H. pinifolia has a minimum concentration of 1000 ppm, while C. rotundata extract is 250 ppm. The results of the identification of bioactive compounds showed that H. pinifolia contains alkaloids, saponins, and steroids, while C. rotundata contains alkaloids.